Importance of Physical Education in School - Abidova Sitora Khurramovna (Scientific Trends, 2025)
Physical education is combined with intellectual, moral, work and aesthetic education. We need to use ped technologies in new ways to interest and increase the interest of the young generation in physical education from the school age. In order to fundamentally improve the teaching of physical education in general secondary schools and ensure the effectiveness of the system of continuous professional development of physical education teachers, to establish a regular improvement of their professional and physical skills.
Keywords: Through physical education classes, students will acquire knowledge and skills on forming a healthy lifestyle. They learn important life principles such as regular exercise, proper nutrition, following a daily routine and giving up bad habits. Physical education at school plays a major role in the physical and mental development of children. Through this subject, students will have the opportunity to live a healthy life, regularly engage in physical activity and develop sports culture.